Exacerbation of delirium and epileptic seizures in an older man with idiopathic Parkinson’s disease due to multiple prescriptions: a case report - Yamaguchi, Takuya; Aihara, Akinobu; Mashiko, Shigeto; Kurosawa, Emiko; Oizumi, Tomoya; Yamagata, Toshihiro; Ishiki, Aiko; Ueda, Juri; Fujikawa, Yuko; Kanno, Atsuhiro; Sumitomo, Kazuhiro; Ohara, Takahiro; et al. (Frontiers in Medicine, 2024)
Introduction Parkinson’s disease (PD) is a disorder characterized by motor symptoms, such as rigidity, akinesia, and resting tremor, as well as non-motor symptoms, including psychiatric manifestations and autonomic failure. The prevalence of PD increases with age, and the condition is more common in men than in women. Conversely, polypharmacy has emerged as a paramount medical concern, especially among older patients, correlating with medicines’ adverse effects, interactions between medicines, frequent admissions to the hospital, and a high risk of morbidity and mortality. Case description We encountered an older male patient with idiopathic PD and mild renal dysfunction. Originally prescribed 14 types of medicines, including anti-PD drugs, the patient developed delirium and epileptic seizures during hospitalization. After reducing the number of medications, including amantadine, the symptoms significantly improved. This clinical course suggests that polypharmacy, in addition to PD itself, poses a significant risk of delirium and epileptic seizures, even in patients with mild renal dysfunction. Conclusion This report is indicative of the risk of polypharmacy and highlights the importance of citing drug interactions for a correct diagnosis in patients presenting with complex symptoms.